Linking soft skills to business education teachers’ job effectiveness in Ilorin metropolis secondary schools - Oluwalola, Felicia Kikelomo; Awodiji, Omotayo Adewale (Journal of Management and Business Education, 2021)
Soft skills are regarded as combination of social, emotional, communication and personal skills which promote workplace effectiveness regardless of qualifications or knowledge acquired. This paper linked soft skills to business education teachers’ job effectiveness. Three research questions guided the study. The study population includes all the secondary school principals, Vice-principals, Heads of Department and students that offer business education-related subjects in Ilorin Metropolis, Nigeria. Random sampling and stratified techniques were used to select 316 participants. We used adapted structured questionnaires tagged “Teachers’ Soft Skills Questionnaire (TSSQ)” and Business Education Teachers’ Job Effectiveness Questionnaire (BETJEQ). We used descriptive statistics to answer the research questions and Pearson Products Moment Correlation (PPMC) to test hypotheses. We found the level of business education teachers’ soft skills and their job effectiveness to be high at 70.6% & 64.6 %. Also, the result revealed a strong, positive linkage between the two variables, r = 0.866, n = 316, p < .000. By implication, Soft Skills will promote teachers’ job effectively positively. That is, the higher the soft skills in the teachers, the better their effectiveness. Therefore, we recommended for practice based on the findings that special training in form of workshop should be organised for Business education teachers on regular basis by government in collaboration with professional bodies to promote up-to-date soft skills that are transferable and promote teaching effectiveness.